THE ISSUE OF IMITATION OF SCIENTIFIC PUBLICATION ACTIVITY IN RUSSIA AND RECOMMENDATIONS FOR SOLVING IT - O. A. Yeremchenko; F. A. Kurakov (Ekonomika Nauki)
The article demonstrates that the imitation of scientific publication activity is increasingly becoming a critical problem in the field of Russian science management. It is driven, on one hand, by increased demand from the expected growth in publication activity among the employees of Russian scientific and educational organisations and, on the contrary, by the absence of mechanisms of self-regulation of a domestic scientific community. This article explores methods, most frequently used for falsification of the publication activity inRussia. A conclusion is drawn from it about the necessity to develop mechanisms of self-regulation in the field of publication activity of Russian research and to increase the norms of publication and editorial ethics of Russian practices.